Peptidomic discovery of short open reading frame–encoded peptides in human cells - Slavoff, Sarah A; Mitchell, Andrew J; Schwaid, Adam G; Cabili, Moran N; Ma, Jiao; Levin, Joshua Z; Karger, Amir D; Budnik, Bogdan A; Rinn, John L; Saghatelian, Alan (Nature chemical biology, 2013)
The human genome contains stretches of DNA sequence with unknown function. Peptidomics coupled to RNA-Seq now reveals a class of short open reading frames in human genomes that are translated into small peptides. The complete extent to which the human genome is translated into polypeptides is of fundamental importance. We report a peptidomic strategy to detect short open reading frame (sORF)-encoded polypeptides (SEPs) in human cells. We identify 90 SEPs, 86 of which are previously uncharacterized, which is the largest number of human SEPs ever reported. SEP abundances range from 10–1,000 molecules per cell, identical to abundances of known proteins. SEPs arise from sORFs in noncoding RNAs as well as multicistronic mRNAs, and many SEPs initiate with non-AUG start codons, indicating that noncanonical translation may be more widespread in mammals than previously thought. In addition, coding sORFs are present in a small fraction (8 out of 1,866) of long intergenic noncoding RNAs. Together, these results provide strong evidence that the human proteome is more complex than previously appreciated.